Disease investigation on Hepatitis B and C, and Tuberculosis Awareness - Sufianu, Temitope (My University)
Hepatitis is a liver inflammation caused by hepatitis viruses, autoimmune diseases, and drugs, among other factors. In the United States, the incidence rate of chronic hepatitis C in 2021 was reported to be 56.7 cases per 100,000 people, while the acute hepatitis C incidence rate was 1.3 cases per 100,000 population. Chronic hepatitis B virus incidence in 2021 was 5.9 per 100,000 people, while acute hepatitis B virus was 1.0 per 100,000 population (CDC, 2021). The World Health Organization stated that the hepatitis B virus and hepatitis C virus are responsible for 1.1 million deaths worldwide in 2019 (Philippa et al., 2021). Hepatitis causes liver damage, cirrhosis, and liver cancer, contributing to nearly one-fourth of all patient deaths (CDC, 2021). Tuberculosis is an infectious disease that most often affects the lungs and is caused by Mycobacterium tuberculosis. Latent tuberculosis infection is an infection with Mycobacterium tuberculosis in which the bacteria are alive but contained by the immune system. However, it is not infectious when compared to active tuberculosis. The estimated prevalence of latent tuberculosis infection in the United States is 5.0% (13 million individuals) (Mangione et al., 2023). EpiTrax was a significant tool for investigating communicable diseases, environmental hazards, and bioterrorism threats. In this report, data of probable and confirmed hepatitis C cases in Wyandotte County, Kansas, were obtained and analyzed from the EpiTrax tool and then graphically represented. In this report, data of probable and confirmed hepatitis C cases in Wyandotte County, Kansas, were obtained and analyzed from the EpiTrax tool, and then, graphically represented, showing the total number of cases, ethnicity, race, age, gender, case status, and outcomes. In addition, interventions performed for patients with unfavorable outcomes were indicated. Also, I consulted the Data informaticist, the Public information officer, the tuberculosis case manager, the perinatal hepatitis B prevention program coordinator, and the chief epidemiologist for meaningful information. The purpose of the project was to create awareness of these diseases for the residents of Wyandotte County. In attaining my objectives, I observed several determinant factors influencing the transmission of diseases among the residents through community outreach and clinical meetings. Flyers and posters were the tools for primary interventions used to create awareness within the county.
Keywords: Hepatitis; Tuberculosis; EpiTrax; Disease investigation; Awareness; Wyandotte County